Functional Responses of Bird Assemblages to Land-Use Change in the Colombian Llanos Region - Rincon-Parra, Victor Julio; Echeverry-Galvis, María Angela; Alvarez, Silvia J. (Frontiers in Environmental Science, 2022)
Land-use change in the Colombian Llanos due to agro-industrial expansion affects biodiversity. This change alters species occurrence probability, ultimately impacting species’ composition. For some species, occurrence probability increases with land-use change while it stays unchanged or decreases for others. This interspecific variation in responses to land-use change may be mediated by differences in traits’ attributes, among other factors. We investigated the influence of traits’ attributes on the response to land-use change in terms of occurrence probability, for bird species in the Colombian Orinoquia region. We compiled data for 13 morphological and life-history traits of 364 species recorded in forests, savannas, rice fields, palm oil crops and livestock pastures, in the piedmont and flooded savanna landscapes. We used a novel framework to identify response functional traits (i.e., traits with a significant effect on occurrence probability) through multiple statistical tests. We used random forest models to identify functional traits for pairwise comparisons of natural vs. agricultural land use types. For the functional traits we estimated the influence of their attributes on species’ responses to land-use change. We identified functional groups based on hierarchical clustering analysis. Functional groups corresponded to different levels of response, i.e., different changes in probability occurrence. Land-use change altered the multidimensional space of bird traits (i.e., functional diversity), implying modifications in species composition, functional redundancy, and functional group turnover. Functional traits were similar for random forest classifications of the same natural cover but differed among landscapes. In the piedmont forests, social behavior - migratory status was a functional trait combination common to all classifications while foraging behavior - nest location was common to all forests in flooded savanna classifications. Migratory status was a functional trait for all savannas classifications. Functional groups provided a description of the impacts of land-use change on bird assemblages. Identification and characterization of these groups using trait attributes can help predict species responses to land-use change and guide conservation efforts towards groups with decreased occurrence probability, including recommendations for agricultural practices that can reduce impacts on the Orinoquia biodiversity.